Chasing the City : Models for Extra-Urban Investigations - Nason, Joshua M; Nesbit, Jeffrey S; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Historically, many architects, planners, and urban designers solicit idealistic depictions of a controllable urban environment made from highly regulated geometrical organizations and systematically defined processes. Rather than working as urban "designers" who set out to control and implant external processes, we shift our approach to that of urban "detectives," who set out to chase the city. Charged with approaching the city more responsively, we investigate what we do not know, allowing the city to direct our work. As urban detectives, we have the ability to interrogate and respond to the elaborate patterns emerging from self-generated, internalized urban interactions. Chasing the City asks what are the current design trends shaping how we, first, understand the cities of today to, then, produce informed decisions on the continuously undefined evolving city of tomorrow. Intentionally, the work here does not adhere to rudimentary notions of supposed singularities or rely upon past generations of idealistic utopian models. Rather, Chasing the City delineates current models of urban investigation that seek to respond to the nature of cities and develop heretofore-urban strategies as concurrently negotiated future urbanism. This edited volume provides a collection of innovative design research projects based on shared notions of Chasing the City through three bodies of strategic frameworks: (1) Mapping, (2) Resource, and (3) Typology. This structure ultimately allows readers, as fellow urban detectives, access to exploratory tools and methods of detection that accumulate from our environs, both practical and projective in our chase of the city.
Acknowledgements -- Notes on Contributors -- Foreword: Chasing the City in the Age of New Geography -- David Grahame Shane -- Chapter 1: Introduction: Chasing the Neo-utopian Paradox -- Joshua M. Nason and Jeffrey S. Nesbit -- Chapter 2: Chasing the Awkward City -- Joshua Nason -- Chapter 3: Chasing #Antidrone -- Derek Hoeferlin -- Chapter 4: Chasing the Logistical City and Its Spatial Formations -- Clare Lyster -- Chapter 5: Chasing and Rewiring Resource Territories -- Neeraj Bhatia -- Chapter 6: Chasing Military Logistics in the Urban Void -- Jeffrey S. Nesbit -- Chapter 7: Chasing Lines of Engagement -- Edward Becker -- Chapter 8: Chasing Strategies for the Post-crisis -- Emmanuelle Chiappone-Piriou -- Chapter 9: Chasing Ambiguous Conditions of Coexistence -- Peter Winston Ferretto -- Chapter 10: Chasing a Genealogy of X -- Choon Choi -- Afterword: Chasing Composition -- David Salomon -- Index
Includes bibliographical references and index.
Also available in print format.
Keywords: Cities and towns -- Forecasting; City planning -- Forecasting; Electronic books